The Politics of Transportation Services in Suburban Montreal: Sorting Out the "Mile End Muddle," 1893–1909 - Boone, Christopher (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1996)
The rapid spread of electric streetcar technology in the 1890s brought not only passengers to the suburbs but streetcar politics too. Beyond Montreal's city limits in the Village of Mile End, the politics of streetcar services was particularly virulent and indeed often comical. The contest between competing streetcar firms, and divisions within the council, culminated in early March 1893 when the Mayor of Mile End tore up a half-mile of the Montreal Street Railway Company's track. Though residents had long clamoured for streetcar service, most applauded the Mayor's heroics. This paper is an attempt to make sense of the 'Mile End Muddle,' as the newspapers dubbed the strange sequence of events, and to explain the relative weakness of the council and residents in the contest for streetcar service. I aim to show that the council and residents of Mile End, though vociferous and often violent, were unable to secure any significant degree of control of the actions of the MSRC and the Park & Island Railway Company. Although Mile End had the legal right, as a municipal corporation, to regulate streetcar services in its domain, in practice it and its venal councillors were small players in the battle for a streetcar franchise. Without the tax base to threaten public ownership of streetcar services, the town of Mile End was unable to defy the interests of heavily capitalized streetcar companies. By dividing the territory of greater Montreal between them, the MSRC and Park & Island effectively undermined the negotiating power of suburban councils to regulate a critical urban service.